PENGALAMAN REMAJA TERKAIT PENGGUNAAN GADGET DALAM MEMATUHI ATURAN ORANG TUA - Amelia Ole, Anita; Gabriella Alleid Dian Baureh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of technology has made gadgets an integral part of teenagers' daily lives. Even though they offer various benefits, excessive use of gadgets can have negative effects, so parental supervision is needed. The purpose of this study is to describe teenagers' experiences in complying with parental rules regarding gadget use. This study uses a qualitative approach with a case study method. The research subjects were teenagers aged 11 to 13 years old attending several schools in Southeast Minahasa Regency. Data were collected through structured interviews and observations, and then analyzed qualitatively. The results show that all informants use gadgets every day for about 2 to 4 hours to communicate, study, play games, watch videos, and participate in religious activities. Parents provide various forms of supervision, such as limiting the time children spend using gadgets, checking the gadgets their children have used, confiscating their gadgets if rules are broken, and giving advice or punishment, which are forms of parental guidance for children. Most teenagers feel annoyed, disturbed, or angry when being supervised by their parents while using gadgets or when their gadgets are taken away. But after these incidents, teenagers understand the purpose of parental supervision, which is to protect them from excessive gadget use and to build more disciplined habits. This research shows that parental supervision plays an important role in helping teenagers develop wiser and more responsible gadget use.